Alcohol use, cannabis use, and psychopathology symptoms among college students before and after COVID-19. (October 2021) - Schepis, Ty S.; De Nadai, Alessandro S.; Bravo, Adrian J.; Looby, Alison; Villarosa-Hurlocker, Margo C.; Earleywine, Mitch; ,
Abstract: College students have experienced significant disruptions related to COVID-19, and limited international data suggest they may be at elevated risk for mental health symptom increases related to COVID. Given their potentially elevated risk, our aim was to evaluate differences from pre-college closures to post-closure in mental health symptoms, alcohol, and cannabis use. Participants (N = 4749) were from seven U.S. public universities/colleges. They were 70.1 % female and 48.5 % white, non-Hispanic/Latino, with 48.1 % in their first college/university year. 30-day retrospective assessments of alcohol and cannabis use, and past 2-week retrospective assessments of anxiety, depression, anger, and insomnia were captured at the time of the survey. We examined differences between those providing data pre- and post-university closure via linear and negative binomial regressions. Alcohol and cannabis use days were 13 % and 24 % higher, respectively, from pre-to post-university closure; also, prevalence of any 30-day alcohol use and alcohol use consequences were both higher in the post-closure sample (odds ratios = 1.34 and 1.31, respectively). In contrast, days of binge alcohol use were 4 % lower in the post-closing sample. Depressive symptoms and anger were both modestly higher in post-closing participants ( d  < 0.1), with no differences in anxiety symptoms or insomnia. The modest differences in substance use and mental health from pre-closure through two months post-college closure suggest unexpected resilience in a large and diverse sample of students. College health providers will need to identify those students experiencing the greatest increases in mental health symptoms and substance use, using innovative outreach and treatment.